Globalizing India how global rules and markets are shaping India's rise to power - Sinha, Aseema 1966- (Business and public policy, 2016)
"Over the course of the past two decades, India has undergone an enormous transformation which has fascinated many scholars, global leaders and interested observers. In 1990, India was a closed economy and a hesitant and isolated economic power. In 2015, however, India has rapidly risen on the global economic stage; foreign trade now drives more than half of the economy and Indian multi-nationals actively pursue global alliances. Focusing on second-generation reforms of the late 1990s, Aseema Sinha explores what facilitated this rapid change in a self-reliant country predisposed to nationalist ideas. Drawing on fieldwork undertaken in Geneva, New Delhi and Washington DC, alongside a close analysis of the textile and pharmaceutical industries and a wide range of documentary evidence, the author argues that the impact of globalization on India needs to be understood not just in terms of national policy, but also in terms of India's changing trade capacities and private sector reform"--Provided by publisher.